Synthesis and design of a Generalized Chebyshev low pass prototype microwave filter/ Mohd Firdaus Md Shariff - Md Shariff, Mohd Firdaus (1997)
The function of the filter is to passes only those frequencies in the assigned operating range of the system and rejects all others. The lumped element prototype filters are used as a basis for the realisation of distributed commensurate transmission line filters. The lumped element prototype filters are converted into distributed transmission line filters by using Richard's Transformations. Microwave filters can be designed by approximation equations or by exact synthesis method. This thesis presents the synthesis and design of a Generalized Chebyshev low-pass prototype microwave filter. The synthesis of prototype networks is done by using Maple V mathematical software. It was then analysed and optimised on HP/ESSOFT Libra software. The prototype was designed with a cut-off frequency of 4 GHz, stopband attenuation of 60 dB and a return loss of 20 dB.